2023
DOI: 10.3389/fpubh.2023.1136744
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequality in the worsening of psychosocial wellbeing via disrupted social conditions during COVID-19 among adolescents in Hong Kong: self-resilience matters

Abstract: BackgroundAdolescents, especially the socioeconomically disadvantaged, are facing devastating psychosocial impact of the COVID-19 pandemic during their critical developmental period. This study aims to (i) examine the socioeconomic patterning of the worsening of psychosocial wellbeing, (ii) delineate the underlying mediating factors (i.e., overall worry about COVID-19, family's financial difficulty, learning problems, and loneliness), and (iii) explore the moderating effect of resilience in the inter-relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Equaling 12, by far the greatest number of included articles that were returned, as evident from Table 1, were those that found self-directed learning, online learning, and mental health negative for public school students during COVID-19. These publications are on the following topics: learning in isolation [67]; High school student-athlete experiences [68]; Self-directed learning and attitude on online learning [69]; School connectedness still matters [70]; Implementation and challenges of online education [71]; Student evaluations of transitioned-online courses [72]; The impact of learning on science, social, and digital literacy [73]; A comparison of online learning challenges [74]; "Teachers act like we're robots" [75]; Socioeconomic inequality [76]; High school physical education teachers' perceptions [77]; and The home-school linkage [78].…”
Section: All Negativementioning
confidence: 99%
See 1 more Smart Citation
“…Equaling 12, by far the greatest number of included articles that were returned, as evident from Table 1, were those that found self-directed learning, online learning, and mental health negative for public school students during COVID-19. These publications are on the following topics: learning in isolation [67]; High school student-athlete experiences [68]; Self-directed learning and attitude on online learning [69]; School connectedness still matters [70]; Implementation and challenges of online education [71]; Student evaluations of transitioned-online courses [72]; The impact of learning on science, social, and digital literacy [73]; A comparison of online learning challenges [74]; "Teachers act like we're robots" [75]; Socioeconomic inequality [76]; High school physical education teachers' perceptions [77]; and The home-school linkage [78].…”
Section: All Negativementioning
confidence: 99%
“…A paper focusing on socioeconomic inequities during COVID-19 [76] found that students from lower socioeconomic living conditions lacking resilience necessarily had a negative response to self-directed learning and online learning, and had their mental health suffer during COVID-19. Students from other socioeconomic brackets similarly required resilience to overcome problems in these three areas but they were more likely to demonstrate it during the pandemic.…”
Section: All Negativementioning
confidence: 99%